(untitled) (Literatures of the World: Poetics, Mentality and Spirituality, 2014)
The purpose of this article is to attempt to identify the depth and essential functions of each of the components of the two triads: basic natural and social dependences of talent from memory, mastery from culture and genius – from the strength of will of man.